Coronary artery profile on coronary angiography in TMT positive female patients presenting in BPKIHS, Nepal - Thapa, Rajan; Karki, Prahlad; Pandey, Naveen Kumar; Ghimire, Jeet Prasad; Pandey, Brijesh; Gyawali, Achyut; Shrestha, Sanjay; Thapa, Bhuwan; Chaurasia, Pawan; Thapa, Malati (Journal of Advances in Internal Medicine, 2024)
BACKGROUND Diagnosis of Coronary artery disease by Coronary artery angiography is limited by its availability, cost and as an invasive procedure. Treadmill test is a noninvasive and easily available test for diagnosing as well as prognosis of coronary artery disease and is most commonly performed stress test for diagnosis of coronary artery disease. Women tend to have a greater release of catecholamines during exercise, which could potentiate coronary vasospasm and augment the incidence of abnormal exercise results. TMT in women have a relatively low diagnostic yield for CAD compared to men, especially when symptoms are atypical or non-specific. AIM AND OBJECTIVE To analyze the coronary artery profile on Coronary Angiography (CAG) in TMT positive female patients. METHODS This was a cross sectional observational study carried out over a period from 15th July 2024 to 15th October 2024 in Department of Cardiology. A total of 64 female patients with positive Treadmill test and underwent CAG after pre-test probability Results: A total of 64 patients were enrolled in the study. The mean age of the patient was 53.38±16.7 years. Hypertension was present in (43.8%) study female as must common risk factors. DM female patient was 35.9% study patients. Dyslipidemia was seen in 34.4% patients. CAD was seen in 29.7% of cases with significant CAD in 18.97% study patients. The most common coronary artery involved having significant disease during coronary angiogram was LAD in 38.89% of cases with CAD. Two third of patient who had CAD was at high pre-test probability categories. CONCLUSIONS TMT has a low predictive value of CAD in female patients except those female TMT positive patients with a high pre-test probability score.